2017
DOI: 10.1111/jcpe.12787
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between tooth loss and peripheral arterial disease among women

Abstract: Aim We assessed the longitudinal association between tooth loss and peripheral arterial disease (PAD) within the Nurses’ Health Study. Materials and Methods After excluding participants with prior cardiovascular diseases, 277 out of 79,663 women were confirmed as PAD cases during 16-years of follow-up. Number of teeth and recent tooth loss were reported initially in 1992. Subsequent tooth loss was recorded in 1996 and in 2000. We evaluated the associations of baseline number of teeth and recent tooth loss wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 38 publications
2
26
1
Order By: Relevance
“…Asai et al reported an association between tooth loss and the degree of arterial stiffness in 8124 participants. Muñoz‐Torres et al reported that tooth loss showed a modest association with peripheral arterial disease. Takeuchi et al reported associations between tooth loss and dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Asai et al reported an association between tooth loss and the degree of arterial stiffness in 8124 participants. Muñoz‐Torres et al reported that tooth loss showed a modest association with peripheral arterial disease. Takeuchi et al reported associations between tooth loss and dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Tooth loss can also impact facial appearance and therefore affect self‐esteem and socialization . Other systemic conditions, such as cognitive decline and peripheral arterial disease, as well as overall mortality, have been linked to tooth loss. Financial limitations have also been linked to reduced oral healthcare utilization among older adults in multiple countries, and increased oral health insurance coverage is associated with higher use of oral healthcare services …”
Section: Introductionmentioning
confidence: 99%
“…To clarify the meaning of tooth loss in the epidemiologic context, it would be helpful to use longitudinal data. A few studies report on tooth survival over time or trends in repeated cross-sectional samples [14][15][16][17][18][19] but most rely on self-reported tooth loss with limitations in validity, 14,16,17 or are performed in selected patient groups with limitations in generalizability into the general population. 19,20 To date, the largest published longitudinal analysis of changes in dental status comes from the Dunedin study, a prospective cohort study of approximately 1000 participants born in 1972/1973.…”
Section: Introductionmentioning
confidence: 99%